2019
DOI: 10.1038/s41598-019-47538-1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influence on calcification of the bivalve Chamelea gallina along a latitudinal gradient in the Adriatic Sea

Abstract: Environmental factors are encoded in shells of marine bivalves in the form of geochemical properties, shell microstructure and shell growth rate. Few studies have investigated how shell growth is affected by habitat conditions in natural populations of the commercial clam Chamelea gallina . Here, skeletal parameters (micro-density and apparent porosity) and growth parameters (bulk density, linear extension and net calcification rates) were investigated in relation to shell sizes and envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 47 publications
4
33
2
Order By: Relevance
“…According to our findings, the two shell sectioning techniques were equally reliable, whereas the shell surface growth ring approach underestimated age. Indeed, the approach has yielded contrasting results in various bivalve species, either underestimating (Gaspar et al, 2004;Hernández-Otero et al, 2014) or overestimating age (Gaspar et al, 1995; Peharda et al, 2002), despite the occasional success (Mancuso et al, 2019). In our study, underestimation was due to the large amount of shells presenting a smooth surface with no clefts, independently from the size, which led to a mismatch with the length-at-age data derived from the internal readings.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…According to our findings, the two shell sectioning techniques were equally reliable, whereas the shell surface growth ring approach underestimated age. Indeed, the approach has yielded contrasting results in various bivalve species, either underestimating (Gaspar et al, 2004;Hernández-Otero et al, 2014) or overestimating age (Gaspar et al, 1995; Peharda et al, 2002), despite the occasional success (Mancuso et al, 2019). In our study, underestimation was due to the large amount of shells presenting a smooth surface with no clefts, independently from the size, which led to a mismatch with the length-at-age data derived from the internal readings.…”
Section: Discussioncontrasting
confidence: 59%
“…Several factors, including spawning, food availability, type of substratum, depth, light, temperature, salinity and population density may affect shell growth rate (Gaspar et al, 2004;Dalgiç et al, 2010). Growth is the result of linear extension along the umbonal-ventral axis per unit of time, and slows down with increasing age or size (Lorrain et al, 2004), as also confirmed by isotope analysis (Keller et al, 2002;Mancuso et al, 2019).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…There are significant differences in δ 13 C variability between juvenile (<1 mm) and (>1 mm) adult pteropod shells (F = 3.60, p = 0.0087) which may indicate the presence of a metabolic vital effect ( Figure 4B). The isotopic composition of scallop specimens displaying high growth rates has been found to deviate more from isotopic equilibrium than specimens with slower growth rates (Owen et al, 2002), and several studies have found that growth rates decrease and become less variable with age (Schöne et al, 2005;Butler et al, 2010;Mancuso et al, 2019). Assuming similar relationships occur in pteropods, the increased variability in δ 13 C of juvenile pteropods relative to adults could be attributed to higher growth rates in smaller specimens.…”
Section: Deciphering Pteropod δ 13 Cmentioning
confidence: 99%